ANALISIS KAMPANYE SOSIAL PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KAMPUNG PANGAN INOVATIF YANG DISELENGGARAKAN PT KPI RU III PLAJU KOTA PALEMBANG - Eva Kurnia, Siti Rachmi Indahsari, Binsar Butar-Butar (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2022)
Social campaigns are a series of non-commercial planned communication processes within a certain period of time that contain messages about social problems that occur in the community such as community empowerment, this is in synergy with the program run by CSR PT KPI RU III Plaju which is implemented in the